Effect of elevated carbon-dioxide on plant growth, physiology, yield and seed quality of chickpea (Cicer arietinum L.) in Indo-Gangetic plains - Lamichaney, Amrit (Physiol Mol Biol Plants, 2021)
In the present scenario of climate change with constantly increasing CO(2) concentration, there is a risk of altered crop performance in terms of growth, yield, grain nutritional value and seed quality. Therefore, an experiment was conducted in open top chamber (OTCs) during 2017–18 and 2018–19 to assess the effect of elevated atmospheric carbondioxide (e[CO(2)]) (600 ppm) on chickpea (cv. JG 14) crop growth, biomass accumulation, physiological function, seed yield and its quality in terms of germination and vigour. The e[CO(2)] treatment increased the plant height, leaf and stem biomass over ambient CO(2) (a[CO(2)]) treatment. The e[CO(2)] increased seed yield by 11–18% which was attributed to an increase in the number of pods (6–10%) and seeds plant(−1) (8–9%) over a[CO(2)]. However, e[CO(2)] reduced the seed protein (7%), total phenol (13%) and thiobarbituric acid reactive substances (12%) and increased the starch (21%) and water uptake rate as compared to seeds harvested from a[CO(2)] environment. Exposing chickpea plant to e[CO(2)] treatment had no impact on germination and vigour of the harvested seeds. Also, the physical attributes, total soluble sugar and antioxidant enzymes activities of harvested seeds were comparable in a[CO(2)] and e[CO(2)] treatment. Hence, the experimental findings depict that e[CO(2)] upto 600 ppm could add to the growth and productivity of chickpea in a sub-tropical climate with an implication on its nutritional quality of the produce.